Settlement of Sexual Violence Cases Against Boys with Bisexual Perpetrators in Wonogiri from a Justice Perspective - Marisa Kurnianingsih; Elisa Rachmawati; Kuswardani Kuswardani; Hartanto Hartanto (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2025)
This research was conducted to find out how sexual violence against boys with bisexual perpetrators in Wonogiri is resolved. Sexual violence is now widespread and increases every year. The perpetrators of sexual violence are mostly adults, and the victims are girls, but currently, many boys are also victims of sexual violence. In Wonogiri in 2021, there were cases of sexual violence involving bisexual perpetrators and male victims. This research aims to provide an explanation regarding the resolution of cases of sexual violence against boys with bisexual perpetrators in Wonogiri using empirical juridical writing methods, with the type of research using descriptive research, with primary and secondary data sources, and using observational data collection methods. and interviews. This research was carried out at the Wonogiri Police Office, Criminal Investigation Unit, and Wonogiri Regency PPA Unit, and an analysis was carried out of court decisions regarding the judge's consideration of the impact of sexual violence on victims in making their decision. Based on research, it was found that the handling of sexual violence cases was carried out by the Wonogiri Regency PPA Unit, and in court decisions, it was discovered that the victims of sexual violence with bisexual perpetrators were traumatized by the incident, so that it was used as a basis for criminal charges by the judge.